2021
DOI: 10.1093/nar/gkab134
|View full text |Cite
|
Sign up to set email alerts
|

DOCK7 protects against replication stress by promoting RPA stability on chromatin

Abstract: RPA is a critical factor for DNA replication and replication stress response. Surprisingly, we found that chromatin RPA stability is tightly regulated. We report that the GDP/GTP exchange factor DOCK7 acts as a critical replication stress regulator to promote RPA stability on chromatin. DOCK7 is phosphorylated by ATR and then recruited by MDC1 to the chromatin and replication fork during replication stress. DOCK7-mediated Rac1/Cdc42 activation leads to the activation of PAK1, which subsequently phosphorylates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…DOCK7 is a RAC-GEF with the potential to regulate F-actin organization (Fig. 5 A), consistent with previous publications reporting DOCK7-mediated RAC1/CDC42 - PAK1 activation in the DNA replication stress response 122 , and the promotion of glioblastoma cell invasion by DOCK7 via RAC activation 123 . These findings identify the LPAR2 → DOCK7 axis as a novel signaling mechanism regulating actomyosin dynamics to be of similar relevance in the initiation of entosis as LPAR1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…DOCK7 is a RAC-GEF with the potential to regulate F-actin organization (Fig. 5 A), consistent with previous publications reporting DOCK7-mediated RAC1/CDC42 - PAK1 activation in the DNA replication stress response 122 , and the promotion of glioblastoma cell invasion by DOCK7 via RAC activation 123 . These findings identify the LPAR2 → DOCK7 axis as a novel signaling mechanism regulating actomyosin dynamics to be of similar relevance in the initiation of entosis as LPAR1.…”
Section: Discussionsupporting
confidence: 91%
“…8 E and 9 A). These observations may be clinically significant in view of the reported overexpression of DOCK7 in OC 122 and the inverse association of MYPT1 expression with HGSC survival ( Fig. S13 ).…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that RPA1 phosphorylation upon RS decreases the ubiquitination of chromatin-loaded RPA1, leading to an accumulation of RPA1 on stalled replication forks. This helps the DNA-binding domains of RPA2 to bind with RPA1-coated ssDNA, thus contributing to increased RPA2 binding stability (85). Loss of RPA accelerates fork breakage, whereas overexpression of RPA is sufficient to delay a "replication catastrophe" (86).…”
Section: Rpamentioning
confidence: 99%
“…More recently, it was shown that Dock7 was essential for the survival of ovarian cancer cells after DNA damage and replication stress induced by chemotherapy. Gao, et al showed Dock7 activated Cdc42 and Rac in the nucleus to ensure proper replication stress response through the stimulation of the serine/threonine protein kinase Pak1 69 . Here, we highlight an important new role for Dock7, where it potentiates AKT activity within a distinct mTOR signaling complex to maintain a malignant phenotype and cell survival during stresses like those observed within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%